A Study on Link Adaptation Techniques for IEEE 802.11bd Based eV2X Communications - Anwar, Wagar; Franchi, Norman; Fettweis, Gerhard (IEEE Vehicular Technology Conference, 2021)
The ultra-high reliability is an essential requirement for enhanced vehicle-to-everything (eV2X) use cases. In order to ensure the desired reliability in a time-varying channel, link adaptation is required. Therefore, the current and upcoming technologies use adaptive modulation and coding (AMC) schemes. By using AM C, the reliability and data rates could be adapted according to the channel conditions. To further improve reliability, concepts like multi-connectivity could also be used. In multi-connectivity, redundant data can be transmitted using multiple simultaneous links and combined at the receiver to improve reliability. However, this requires link adaption in terms of both numbers of multiple links and AMC. In this paper, we evaluate different link adaptation schemes for IEEE 802.11bd based on single-link and multi-connectivity communications. For single-link communications, we generate channel quality indicators (CQI) based on various signal-to-interference-plus-noise ratio (SINR) mapping techniques, e.g., exponential effective SINR mapping (EESM), received bit information rate (RBIR), and recently proposed enhanced EESM (eEESM). The performance of these schemes is evaluated in terms of achieved reliability and data rates. Results show that eEESM achieves close to optimal performance. In the case of multi-connectivity, different MCS and link adaptation schemes are evaluated. It is shown that joint adaptation of MCS and the number of links deliver better performance in terms of data rates and link utilization.
Created from Fastlane, Scopus look-up
Keywords: 5G and beyond; Adaptive Modulation and Coding; IEEE 802.11bd; Link adaptation; Multi-connectivity